Molecular analysis of parturition via oxytocin receptor expression - Tadashi Kimura; Kazuhide Ogita; Kei-ichi Kumasawa; Takuji Tomimatsu; Tateki Tsutsui (Elsevier, 2013)
In daily obstetric practice, oxytocin is one of the most frequently used drugs to stimulate uterine contraction. However, uterine sensitivity to oxytocin is profoundly different among pregnant women, which may reflect oxytocin receptor (OTR) expression in the uterus. We review here the literature focusing on OTR regulation in the human uterus. Recent progress in molecular biology has augmented our knowledge about OTR regulation in the uterus at the transcription level, although the totality of preparation for labor through OTR expression is still obscure.